Enhancing the performance of beech-timber concrete hybrids by a wood surface pre-treatment using sol-gel chemistry. Issue 9 (September 2018) - Kostić, Sanja; Meier, Sandro; Cabane, Etienne; Burgert, Ingo
Abstract: Timber-concrete composites require reliable connections between both components, which are usually obtained by metal fasteners or slots in the wood. In this study, an alternative approach is presented based on a fully glued connection in combination with a primer treated wood surface, to enhance the compatibility and the adhesion properties at the interface between beech wood and concrete. Prior to the gluing and the concrete application in a wet-on-wet process, the wood surface was functionalised with a xerogel obtained by means of a sol-gel process, consisting of two layers of silane nanofilms, with different functional groups, which are capable of undergoing further chemical crosslinking reactions with the adhesive. The coating with its functionalities allows for reducing the penetration of the epoxy adhesives into the wood structure and an additional chemical connection to the adhesive can be established. The main objective of this study was to analyse the effect of the surface treatment on the mechanical properties of such composites in 3-point and 4-point bending tests as well as push-out-tests. The results showed that the pre-treatment can improve the load bearing capacity of the timber-concrete composites, but that a ductile behaviour cannot be achieved with the tested adhesives.